Total Quality Management and Business Performance : The Mediating Role of Competitive Advantage in Palm Oil Production in Lampung Province - Adinda Rizki Indriani; Rr Erlina; Nurul Husna (International Forum of Researchers and Lecturers, 2024)
This study deals with the influence of Total Quality Management (TQM) on business performance through competitive advantage. The purpose of this study is to determine how the influence of Total Quality Management on business performance with competitive advantage as a mediating variable on oil palm fruit producers in Lampung Province. The sample taken in this study was 115 heads of oil palm fruit farmer groups in Lampung Province. Sampling using a non-probability sampling method with random sampling techniques. This study uses a quantitative research type with descriptive statistical analysis and inferential statistical analysis. The method used is Partial Least Square (PLS) and uses SmartPLS 4 software. The results of this study indicate that Total Quality Management (TQM) has a positive and significant influence on business performance and competitive advantage on oil palm fruit producers in Lampung Province. Competitive advantage in mediating is not full because its influence is smaller than the direct influence.